MARKET ECONOMICS PRICING PARTICULARS - V. I. Parshin (Модернизация, инновация, развитие, 2016)
The price performs several economic functions: accounting, stimulation, distribution, demand and offer balancing, serving as production site rational choice criterion, information. Most important pricing principles are: price scientific and purpose-aimed substantiation, single pricing and price control process. Pricing process factors are external, internal, basic (independent on money-market), market-determined and controlling. Different pricing methods and models are to be examined, recommendations on practical application of those chosen are to be written.